RESULTS OF STUDYING HAIRY VETCH (VICIA VILLOSA ROTH) IN MONO- AND BINARY AGROPHYTOCOENOSES AT SPRING PLANTING UNDER THE CONDITIONS OF THE NORTH-EAST OF THE RUSSIAN FEDERATION - T. G. Aleksandrova; O. I. Kovina; T. V. Shelenga; L. Y. Novikova; M. A. Vishnyakova (Труды по прикладной ботанике, генетике и селекции)
Hairy vetch (Vicia villosa Roth), like common vetch (V. sativa L.), is one of the most widespread cultivated forage vetches. In Russia, hairy vetch is sown both in spring and winter planting seasons. V. villosa populations may contain spring, semi-spring, semi-winter and winter biotypes. Three hairy vetch varieties (Nezhnostebelnaya, Siverskaya 2 and Ukrainka) were studied in mono- and binary agrophytocoenosis with oat, rape and barley at spring sowing under the conditions of Leningrad Province of the Russian North-West in 2010-2012. Biotype composition of vetch variety populations was determined to identify adaptive biotypes. Some biological and agronomic characters were analysed. Comparative evaluation of hairy vetch variety populations was performed to test the role of agrophytocoenosis (and its phytocomponent) as a possible factor of biotype variability in vetch varieties and their biological and agronomic characters.